Development finance 2.0: do participation and information technologies matter?. Issue 5 (3rd September 2019) - Singh, J. P.
Abstract: This essay critically examines the discourse of participation in development finance directed at the poor in the Global South from national and international development agencies. This discourse, often termed financial inclusion, posits the ability of development actors to reach the poor involving them in important economic decisions affecting their lives, provides access to products that improve their material conditions, and ensures their credit worthiness through highly nuanced information technology and social media tools. The paper presents evidence from two ethnographically inspired studies undertaken by the author in India and Kenya to ascertain the ways in which the participatory discourse in finance is understood among societal participants themselves. The paper presents relevant epistemes for analyzing what 'grassroots' actors understand as their participation in development-oriented financial inclusion projects. The study forwards two major conclusions: (1) 'habits of authority' among various development actors thwart effective participation; (2) technology platforms that allow for successive innovations and interconnections from businesses and other organizations encourage financial inclusion.